New Media and Children's Social Development: A Case Study of Digital Technology Use among 8–12-Year-Olds in Pakistan - Zubair, Sadaf; Alyousfi, Eyas Aref; Khan, Sajid Ali (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: Technological advances have accelerated the pervasive use of new media among children, significantly influencing their social interaction patterns. This study examines the impact of new media usage on the social behaviors of children aged 8–12 years in Pakistan, a developing country context that remains underexplored in the global discourse on digital childhoods. Methodology: Employing a sequential explanatory mixed-methods approach, 220 children were purposively sampled. Quantitative data were collected using a validated questionnaire and analyzed using SPSS 21, followed by qualitative interviews with selected participants and teachers to enrich the findings. Main Findings: The results revealed that 59.6% of children demonstrated “good” and 24.5% “very good” new media usage competencies. In terms of social interaction, 64.6% exhibited strong interpersonal skills. Regression analysis indicated that new media usage significantly explained 64.3% of the variance in social interaction patterns (R² = 0.643, p = 0.015). Interviews revealed a nuanced picture: while new media enhanced communication, collaboration, and critical thinking, unsupervised and excessive use was associated with tendencies toward social withdrawal and reduced face-to-face engagement. Novelty/Originality of this study: This research provides a new socio-cultural perspective by investigating the dual role of new media in a Pakistan context—highlighting how cultural norms mediate children's digital engagement. Unlike previous studies focused on Western societies, this study integrates both child and teacher voices to propose context-sensitive digital literacy programs and emphasizes family-centered supervision strategies.